2010
DOI: 10.1007/s10228-010-0168-0
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome banding and FISH with rDNA probe in the diploid and tetraploid loach Misgurnus anguillicaudatus

Abstract: The chromosomes of diploid and tetraploid loach, Misgurnus anguillicaudatus, were analyzed by staining with Ag, Chromomycin A 3 (CMA 3 )/Distamycin A (DA), and DA/4',6-diamidino-2-phenylindole (DAPI), and fluorescence in situ hybridization (FISH) with 5.8S + 28S rDNA as a probe. Nucleolus organizing regions (NORs) were mapped to the telomeric region of the short arms of the largest (first) metacentric chromosome pair in diploid loach with 2n = 50 and the homologous quartet in tetraploid loach with 4n = 100. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Karyotyping was conducted according to Levan et al (1964). Differential staining with CMA 3 /DA/DAPI (Schweizer 1976;Schweizer et al 1978) and the Ag-NOR method (Howell and Black 1980) was applied to the chromosome slides in accordance with Li et al (2010). FISH using human 5.8S ?…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Karyotyping was conducted according to Levan et al (1964). Differential staining with CMA 3 /DA/DAPI (Schweizer 1976;Schweizer et al 1978) and the Ag-NOR method (Howell and Black 1980) was applied to the chromosome slides in accordance with Li et al (2010). FISH using human 5.8S ?…”
Section: Methodsmentioning
confidence: 99%
“…In China, bisexually reproducing diploid (2n = 50)-tetraploid (4n = 100) complex exists and thus triploid hybrids are easily produced by cross-breeding (Li et al 2008(Li et al , 2010(Li et al , 2011(Li et al , 2012(Li et al , 2013). Since we observed that meiotic cells most frequently exhibited 25IIs and 25Is in triploid hybrids, we predicted the formation of gametes with a mode at 1.5n (37 or 38) chromosomes as a result of equal segregation of 25IIs and random segregation of 25Is (Li et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The fluorochrome CMA 3 (chromomycin A 3 , Wako)/DA (distamycin A, Sigma) staining was also performed to detect NORs according to Li et al (2010Li et al ( , 2011Li et al ( , 2013. FISH with human 5.8S ?…”
Section: Methodsmentioning
confidence: 99%
“…In Japanese wild populations, no tetraploid loach has been detected (Arai and Fujimoto 2013), but diploid-tetraploid complex exists in Chang Jiang River system in central China (Li et al 2008(Li et al , 2010. Li et al (2012Li et al ( , 2013 verified gonochorisms and sexual reproduction both in Chinese diploid and tetraploid loaches: they reproduce by sexual fertilization of post-meiotic gametes (eggs and spermatozoa) and reciprocal hybridization between diploid and tetraploid produces viable triploid progeny.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation